2022
DOI: 10.1021/acs.jproteome.1c00781
|View full text |Cite
|
Sign up to set email alerts
|

A Method to Estimate the Distribution of Proteins across Multiple Compartments Using Data from Quantitative Proteomics Subcellular Fractionation Experiments

Abstract: Knowledge of cellular location is key to understanding the biological function of proteins. One commonly used large-scale method to assign cellular locations is subcellular fractionation, followed by quantitative mass spectrometry to identify proteins and estimate their relative distribution among centrifugation fractions. In most of such subcellular proteomics studies, each protein is assigned to a single cellular location by comparing its distribution to those of a set of single-compartment reference protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…This result is in line with previous studies, which have shown that proteins can be located and distributed within multiple cellular compartments, e.g., the cytoplasmic fraction can contain cytoplasmic vesicles that may map to membranous-cellular components. 32,[52][53][54][55][56][57][58] Yet, these results, in combination with the Western blots presented in Figure S1, demonstrate that the subcellular fractionation was successful because for most of the subcellular fractions, increases were seen in the identified proteins associated with that cellular component.…”
Section: Different Sample Clean-up Techniques Identify Different Type...mentioning
confidence: 57%
“…This result is in line with previous studies, which have shown that proteins can be located and distributed within multiple cellular compartments, e.g., the cytoplasmic fraction can contain cytoplasmic vesicles that may map to membranous-cellular components. 32,[52][53][54][55][56][57][58] Yet, these results, in combination with the Western blots presented in Figure S1, demonstrate that the subcellular fractionation was successful because for most of the subcellular fractions, increases were seen in the identified proteins associated with that cellular component.…”
Section: Different Sample Clean-up Techniques Identify Different Type...mentioning
confidence: 57%